Research on enterprise terminal network planning under the new retail format. (3rd November 2022) - Zhang, Siqi; Li, Guanyang; Zheng, Yiming; Liu, Yang
In view of the new retail online and offline omni-channel integration, with emphasis on customer consumption experience and delivery timeliness, this paper comprehensively considers customer satisfaction from two aspects of different levels of service costs and delivery timeliness, establishes a bilevel programming model with the maximum comprehensive customer satisfaction and the lowest price of network planning. The paper uses AP clustering algorithm to cluster relevant customer areas, brings the clustering results into the model and applies the NSGA- algorithm for further optimisation. Combined with the analysis of an example, the number, location, scale and service radiation range of the terminal network are planned reasonably, and the network model is innovated. The results show that the model and algorithm can effectively solve the problem of enterprise terminal network planning in the new retail format.